A New Anthraquinone Glycoside from the Heartwood of Cassia auriculata Linn - Rai, K.N.; Kaushalendra, Kumar; Singh, Janardan (Asian Journal of Chemistry, 2010)
The present paper deals with the isolation and structural elucidation of a new anthraquinone glycoside, 3-hydroxy-6, 8-dimethoxy-2-methyl anthraqinone-1-O-β-D-galactoside from the heartwood of Cassia auriculata Linn.